2010
DOI: 10.1159/000312721
|View full text |Cite
|
Sign up to set email alerts
|

Absence of <i>Neisseria meningitidis</i> from Throat Swabs of Kuwaiti Pilgrims after Returning from the Hajj

Abstract: Objective: To investigate whether or not Neisseria meningitidis was present in the throat of Kuwaiti pilgrims after returning from the Hajj. Method: Throat swabs were taken from 177 participants 1 week after returning from the Hajj. The participants were asked about: associated medical conditions, meningococcal vaccination status and the intake of ciprofloxacin before leaving Mecca for Kuwait. Results: There was no throat colonization with N. meningitidis on any of the throat swabs. Of the 177 pilgrims, 163 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Bacterial carriage among Australian Hajj pilgrims latter two studies respectively, 15% and 58.5% pilgrims reported using antibiotics during Hajj [48,49] . Other studies conducted in Iran and Kuwait demonstrated that a single dose of ciprofloxacin before travel essentially eradicated meningococcal carriage [50,51] . The low carriage rate several weeks after Hajj in our study could possibly be indicative of the effect of a fairly high uptake (44.1%) of conjugate meningococcal vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial carriage among Australian Hajj pilgrims latter two studies respectively, 15% and 58.5% pilgrims reported using antibiotics during Hajj [48,49] . Other studies conducted in Iran and Kuwait demonstrated that a single dose of ciprofloxacin before travel essentially eradicated meningococcal carriage [50,51] . The low carriage rate several weeks after Hajj in our study could possibly be indicative of the effect of a fairly high uptake (44.1%) of conjugate meningococcal vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…35,55 From one perspective, chemoprophylaxis can reduce or eliminate the carriage of N. meningitidis, therefore reducing the risk of transmission and disease. 16,56 This is particularly important for pilgrims arriving from the African meningitis belt and all returning pilgrims after Hajj. This is the more relevant given that vaccines currently used by many pilgrims do not have a major impact on carriage and their uptake is variable, especially among locals.…”
Section: Antibiotic Chemoprophylaxismentioning
confidence: 99%
“…In one study, a single dose of ciprofloxacin decreased carriage rate from 8.1% to zero before and after pilgrimage [8]. Of 177 pilgrims, 92% were vaccinated with meningococcal quadrivalent vaccine before the Hajj and 83% received one dose of ciprofloxacin before leaving Makkah and none had N. meningitidis upon return from the Hajj [9]. The current recommendations call for a single dose of ciprofloxacin and ACYW135 meningococcal vaccine for visitors from the African meningitis belt: Benin, Burkina Faso, Cameroon, Chad, Central African Republic, Côte d'Ivoire, Eritrea, Ethiopia, Gambia, Guinea, GuineaBissau, Mali, Niger, Nigeria, Senegal and Sudan [3,10].…”
Section: Introductionmentioning
confidence: 99%